PEMETAAN TINGKAT KETAHANAN PANGAN WILAYAH DI KABUPATEN SIDENRENG RAPPANG - Sri Wahyuni Ali; Mais Ilsan; Ida Rosada (Percetakan Umi Toaha Makassar, 2022)
This research was conducted with the aim to: (1) Identify food security indicators of each sub-district in Sidenreng Rappang Regency. (2) Analyze the level of sub-district food security based on regional food security indicators in Sidenreng Rappang Regency. (3) Mapping food security based on the level of food security of each sub-district in Sidenreng Rappang Regency. This study was conducted with evaluative descriptive methods, supported by quantitafif data and information aimed at better describing the food security conditions of the region related to food security indicators. The analysis unit used is the Subdistrict Scale which uses 20 indicators of the Food Security Index. The results of this study showed that: (1) The level of food security of each sub-district in Sidenreng Rappang Regency varied from various indicators of food insecurity based on Food Availability where almost all sub-districts fall into the category of food resistance with an average score of 5.27, only one sub-district is in the category of food resistance. Food Access with an average score of 4.80 is in the food resistant category. Food absorption with an average score of 5.27 is in the food resistant category. Food Vulnerability with an average score of 4.85 is in the food resistant category. Based on the composite results, it can be produced the Food Defense Map of Sidenreng Rappang Regency can be concluded that in general Sidenreng Rappang regency has Food Resistant status.